Use of Impella Devices for Acute Cardiogenic Shock in the Perioperative Period of Cardiac Surgery - Sicouri,Serge (2022)
ABSTRACT Introduction: The Impella ventricular support system is a device that can be inserted percutaneously or directly across the aortic valve to unload the left ventricle. The purpose of this study is to determine the role of Impella devices in patients with acute cardiogenic shock in the perioperative period of cardiac surgery. Methods: A retrospective single-surgeon review of 11 consecutive patients who underwent placement of Impella devices in the perioperative period of cardiac surgery was performed. Patient records were evaluated for demographics, indications for placement, and postoperative outcomes. Results: Impella devices were placed for refractory cardiogenic shock preoperatively in 6 patients, intraoperatively in 4 patients, and postoperatively as a rescue in 1 patient. Seven patients received Impella CP, 1 Impella RP, 1 Impella CP and RP, and 2 Impella 5.0. Additionally, 3 patients required preoperative venovenous extracorporeal membrane oxygenation (VV-ECMO), and 1 patient required intraoperative venoarterial extracorporeal membrane oxygenation (VA-ECMO). All Impella devices were removed 1 to 28 days after implantation. Length of stay in the intensive care unit stay ranged from 2 to 53 days (average 23.9±14.6). The 30-day and 1-year mortality were 0%. Ten of 11 patients were alive at 2 years. Also, 1 patient died 18 months after surgery from complications of coronavirus disease (Covid-19). Device-related complications included varying degrees> of hemolysis in 8 patients (73%) and device malfunction in 1 patient (9%). Conclusions: The Impella ventricular support system can be combined with other mechanical support devices for additional hemodynamic support. All patients demonstrated myocardial recovery with no deaths in the perioperative period and in 1-year of follow-up. Larger studies are necessary to validate these findings.